Análise de viabilidade, adesão, efetividade e custo de protocolos de reabilitação cardíaca em domicílio para indivíduos com doenças coronarianas assistidos pelo sistema público de saúde - Ana Paula de Lima (2019)
The benefits of cardiac rehabilitation (CR) are already well established, but such intervention has been underused. Poor availability of CR services in health facilities, and other barriers at the system, program, patient, and professional levels make access to these services difficult. In this context, we highlight the incorporation of mobile health technologies and the emergence of home-based CR programs. Available evidence indicates that home-based CR has been considered as an effective CR method that has overcome traditional barriers to participation and provided comparable effects to ambulatory/hospital CR. However, most of these studies were conducted in high-income countries and little evidence exists in low- and middle-income countries (LMIC). Thus, three studies were developed in the present thesis in order to analyze the feasibility, compliance, effectiveness and cost of a home CR protocols for individuals with coronary disease assisted by the public health system in one LMIC. The first article aimed to analyze the feasibility of a specific CR monitoring model at home. It was tested in 10 participants a model that evaluated the electrocardiogram and heart rate through a Holter system, which sent a signal (via bluetooth) to a cell phone and then to a computer station, allowing real-time monitoring. It was identified difficulties in handling the equipment and limitations in connectivity, which made real-time remote monitoring impossible through the proposed model. Thus, a new form of remote CR was established, taking into account the findings of the first study, and an intervention protocol was elaborated and presented as article two in the present thesis. The third article presents the results of the clinical trial that was aimed to verify the compliance, effectiveness and cost of a home-based CR program and compares it with the traditional supervised CR program offered in most Brazilian hospitals. It was performed with 49 coronary artery disease patients, 26 in the traditional CR group (TCR) and 23 in the home CR. It was observed after 3 months that compliance was 61.5% in the TCR group and 73.9% in the home-based CR, with no significant difference between groups (p = 0.357). Both protocols were effective in the other variables, also without differences between the groups. The cost per patient for the service was higher for the RCT group. The equipment used in home CR showed good usability. The third study concluded that home-based CR performed with simple technologies provided similar compliance and effectiveness to the RCT program, but with a lower cost for the service, thus being a viable alternative for PBMR. Taken together, the studies presented in this thesis indicate that the use of technologies may be an alternative of enabling home CR and the continued monitoring of patients by a health professional, increasing the possibility of more patients having access to a systematized CR program.